Play Therapy With Children Survivors Of Tsunami: Malaysia Experience. - Lee, Siew Siew; See, Ching Mey (2005)
Play is the most complete form- of self-expression' developed by,the humanorganism (Landreth, 1991). Play is a child's medium for expression. Play provides a non-threatening and comfortable environment for children to express their unpleasant thoughts and feelings that might become overwhelming.